A rapid, quantitative assay for measuring alkaline phosphatase activity in osteoblastic cells in vitro. - Sabokbar, A; Millett, P; Myer, B; Rushton, N (1994)
Alkaline phosphatase (ALP) is the most widely recognized biochemical marker for osteoblast activity. Although its precise function is poorly understood, it is believed to play a role in skeletal mineralization. The aim of this study was to develop an assay suitable for measuring the activity of this enzyme in microtiter plate format. Using the well-characterized osteoblast-like cell line Saos-2, this paper describes an optimized biochemical assay suitable for measuring ALP activity in tissue culture samples. We have determined that a p-nitrophenyl phosphate substrate concentration of 9 mM provides highest enzyme activities. We have found that cell concentration, and hence enzyme concentration, affects both the kinetics and precision of the assay. We also tested several methods of enzyme solubilization and found that freeze-thawing the membrane fractions twice at -70 degrees C/37 degrees C or freeze-thawing once with sonication yielded highest enzyme activities. The activity of the enzyme decreased by 10% after 7 days storage. This assay provides a sensitive and reproducible method that is ideally suited for measuring ALP activity in isolated osteoblastic cells, although sample preparation and storage can influence results.